Islamic Career Guidance for Increasing Career Insight of Junior High School Students - Sutin Sutin; Hasbi Indra (Prophetic guidance and counseling journal, 2020)
This research is based on the phenomenon of adolescents still in the period of identity search. Teenagers are also still confused in determining their future careers. Adolescent career choices are usually still unstable influenced by the environment and parents. The main problem formulation in this research is the preparation of an effective Islamic career guidance program to increase career insight of students. The purpose of this study is the establishment of an effective Islamic career guidance program to increasing career insight of junior high school students. With this program students are expected to know the potential that exists in him so that he can determine his career in the future. The research method used is qualitative research with the type of field research and Focus Group Discussion (FGD) method. This research was conducted at SMP Sekolah Alam Bogor and SMP N 5 Kota Bogor. The results of this research islamic career guidance program for junior high school students refer to the four program components namely basic services, responsive services, specialization services and individual planning and system support services.